2020
DOI: 10.3390/su12093803
|View full text |Cite
|
Sign up to set email alerts
|

Testing of Commercial Inoculants to Enhance P Uptake and Grain Yield of Promiscuous Soybean in Kenya

Abstract: The aim of this study was to assess the potential of commercial mycorrhizal inoculants and a rhizobial inoculant to improve soybean yield in Kenya. A promiscuous soybean variety was grown in a greenhouse pot study with two representative soils amended with either water-soluble mineral P or rock P to assess product performance. The performance of selected mycorrhizal inoculants combined with a rhizobial inoculant (Legumefix) was then assessed with farmer groups in three agroecological zones using a small-plot, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
(52 reference statements)
0
9
0
Order By: Relevance
“…Mycorrhiza inoculation especially in the field does not always produce positive effects on biomass and grain yield. For example, Faye et al (2020) [ 22 ] showed that inoculating soybean ( Glycine max (L.) Merr .) enhanced root nodulation but had no significant effect on grain yield.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mycorrhiza inoculation especially in the field does not always produce positive effects on biomass and grain yield. For example, Faye et al (2020) [ 22 ] showed that inoculating soybean ( Glycine max (L.) Merr .) enhanced root nodulation but had no significant effect on grain yield.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, for AMF inoculant industry to thrive, rigorous research must be conducted to provide best practices to the inoculant companies regarding composition, quality, quantity, and application methods of the products [ 19 ]. Although lack of efficacy or negative impacts of AMF inoculation has been reported [ 20 , 21 , 22 ], recent studies conducted under field conditions have shown promising results [ 12 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rhizobium inocula are used in both conventional and organic farming, especially for grain legumes [67][68][69][70][71] and were shown to increase N-fixation and soil-N and N/crude protein in grain legume and cereal crops grown after inoculated grass-clover leys [69]. Rhizobium species are legume species-specific and when new legume crops (e.g., soya) are introduced into rotations, treatments of seed with Rhizobium inocula is recommended [71]. The use of Rhizobium inocula was also reported to increase mycorrhizal development from 'natural' mycorrhizal fungal inocula present in soil [70].…”
Section: Rhizobium and Mycorrhizal Fungal Inoculamentioning
confidence: 99%
“…In Kenya, smallholder farmers utilize Rhizatech R inoculant (Table 1) containing a combination of three AMF species produced and distributed by Dudu Tech Ltd company (Faye et al, 2020). In South Africa, Mycoroot (Pty) Ltd produces a number of Mycoroot R branded AMF inoculants that solubilize P, K, Cu, Zn, and Fe, and improve plant tolerance against abiotic stresses.…”
Section: Use Of Nutrient (P K Fe) Solubilizing and Mobilizing Microorganisms As Biofertilizersmentioning
confidence: 99%
“…This explains why microbial inoculants are recommended even in soils with less water and where most nutrients are immobile (Sindhu et al, 2020). In some instances, seed companies and researchers have solved this challenge by producing crop cultivars that customarily favor colonization of specific PGPMs under a wide range of soil conditions (Faye et al, 2020). Through this approach, Gitonga et al (2021) investigated how organic and conventional smallholder farming systems and soybean cultivars (promiscuous vs. non-promiscuous) affect native Bradyrhizobium spp.…”
Section: Development Of Microbial Inocula For Smallholder Farmersmentioning
confidence: 99%